2013
DOI: 10.1016/j.arthro.2013.08.025
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hamstring Autograft Size on Patient-Reported Outcomes and Risk of Revision After Anterior Cruciate Ligament Reconstruction: A Multicenter Orthopaedic Outcomes Network (MOON) Cohort Study

Abstract: Purpose The purpose of this study is to evaluate the effect of graft size on patient-reported outcomes and revision risk following ACL reconstruction. Methods A retrospective chart review of prospectively collected cohort data, 263 of 320 consecutive patients (82.2%) undergoing primary ACL reconstruction with hamstring autograft were evaluated. Graft size, femoral tunnel drilling technique, patient age, sex, and BMI at the time of ACL reconstruction, pre-operative and 2-year post-operative KOOS and IKDC scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
327
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 342 publications
(343 citation statements)
references
References 19 publications
10
327
1
5
Order By: Relevance
“…In 2010, we began performing anatomical single bundle ACL reconstruction with a navigation system, and have successfully restored good knee stability for most of our patients. However, some patient who underwent anatomical single bundle ACL reconstruction with a smaller graft (a graft diameter of <8 mm) experienced poor rotational stability, and this result is similar to the report by Mariscalco et al [11] . Therefore, we must improve the operative methods for anatomical single bundle reconstruction.…”
Section: The Anatomical Double Bundle Acl Reconstruction Technique Wasupporting
confidence: 81%
“…In 2010, we began performing anatomical single bundle ACL reconstruction with a navigation system, and have successfully restored good knee stability for most of our patients. However, some patient who underwent anatomical single bundle ACL reconstruction with a smaller graft (a graft diameter of <8 mm) experienced poor rotational stability, and this result is similar to the report by Mariscalco et al [11] . Therefore, we must improve the operative methods for anatomical single bundle reconstruction.…”
Section: The Anatomical Double Bundle Acl Reconstruction Technique Wasupporting
confidence: 81%
“…Mariscalco MW et al, in their multicentric retrospective chart review of prospectively collected cohort data of 263 patients undergoing primary ACL reconstruction with hamstring autograft, recorded graft size, femoral tunnel drilling technique, patient age, sex, and body mass index at the time of ACL reconstruction, Knee Injury and Osteoarthritis Outcome Score (KOOS) and International Knee Documentation Committee score preoperatively and at 2 years postoperatively; and whether each patient underwent revision ACL reconstruction during the 2-year follow-up period. They found that smaller hamstring autograft size (8mm or smaller) is a predictor of poorer KOOS sport/recreation function 2 years after primary ACL reconstruction [10] . Since most of our patients are doing well at 6 months folIow up, it is too early to predict the graft size and functional outcome of ACL reconstruction of our patients which need longer follow up.…”
Section: Discussionmentioning
confidence: 99%
“…4,9,11 Because hamstring graft diameter is related to a patient's height, mass, and age, 7 success of ACL reconstruction in young, skeletally immature patients relies on additional efforts to prepare a large-diameter ACL autograft. Graft size may also be a concern in adult female patients and persons of short stature.…”
Section: Discussionmentioning
confidence: 99%